Evaluating Hydration Status through Urine Specific Gravity in Children Aged 0–5 Years in Indonesia - Ahmad Thohir Hidayat; Dian Novita Chandra; Dewi Friska; Dwi Noerjoedianto (International Journal of Health Engineering and Technology, 2025)
This study aimed to evaluate the hydration status of preschool children aged 36–72 months in Indonesia using urine specific gravity (USG) and to compare hydration patterns between urban and semi-urban areas. A cross-sectional study was conducted from January to March 2017 among 191 preschool children in East Jakarta and Ambon Island, selected using simple random sampling. Hydration status was assessed through a 7-day USG measurement using a digital pen refractometer, while additional data on demographics, water source, and fluid intake were collected through structured interviews and dietary records. The results showed that 64.9% of children were euhydrated, whereas 35.1% were classified as dehydrated, with no significant difference between Jakarta (34%) and Ambon (36.1%) (p = 0.886). Although 85.9% of households had access to improved water sources, suboptimal hydration persisted, likely due to inadequate fluid intake and limited caregiver awareness. No cases of hyperhydration or severe dehydration were observed. These findings highlight that over one-third of Indonesian preschool children are affected by dehydration, emphasizing the need for regular hydration monitoring and caregiver-focused interventions